Sello y rasgos distintivos del egresado del programa de la Facultad de Derecho de la Universidad de la Costa - CUC (2014)
This article originated from scientific research in a study of the labor impact applied to the graduate program at the University of Law of the Coast in 2013, the construction of a self-assessment within the permanence, constancy, culture exposed administrative and teaching so that in this way improvement plans and strategic actions to strengthen weaknesses, from a defined methodology favors a qualitative approach, under a descriptive, prospective, exploratory survey techniques and instruments are developed questionnaires, population taking as graduates of the program and a sample of 220 190 graduates return the filled out survey instruments material with which the study was performed. Thus, researchers Law Program at the Universidad de la Costa made the study of jobs impact of students who obtained a degree in law from 2006 to 2013 from the categories: General information, employment status, Skills, Education complementary and Level of identification with the institution and impact on the social and academic environment. The investigation becomes an important plans for improving the quality of the program, aiming to strengthen relations between the graduates and the institution, encouraging the pursuit of academic, cultural, social and labor alliances tool. Moreover, it is supported under a theoretical framework consisting of logical concepts docimology, universitología, pedagogy and education management.